The Cytoprotective Effects of Melatonin on Gastric Ulcer: A Rat Model - Muayad, Hela A.; AlQadhi, Huda I. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Gastric ulcer is a prevalent gastrointestinal disorder caused by environmental factors and a higher intake of non-steroidal anti-inflammatory drugs (NSAIDs).Objective: To investigate the prophylactic effects of melatonin on the histology, severity of gastric ulcers, and levels of inflammatory and oxidative stress markers (Interleukin-1beta (IL-1β) and Malondialdehyde (MDA)) in a rat model of indomethacin-induced ulcers.Methods: This study was performed at Al-Mustansiriyah University's Research Center for Cancer and Medical Genetics from November 2023 to May 2024. Fifty healthy male albino rats weighing between 150 - 250 grams were used. After 24 hours of fasting, these rats were divided into five groups, each with 10 rats. Group A: Received 1 ml of indomethacin vehicle (carboxymethylcellulose 1%) orally (negative control). Group B: Received 60 mg/ kg of indomethacin orally (positive control). Group C: Received 20 mg/ kg of omeprazole orally 30 minutes before indomethacin induction. Group D: Received 20 mg/ kg of melatonin solution orally 30 minutes before indomethacin induction. Group E: Received 30 mg/ kg of pioglitazone solution orally. After 1 hour, rats received a melatonin solution of 20 mg/ kg and waited for 30 minutes before induction.Results: The group that received melatonin pretreatment at a dosage of 20 mg/kg exhibited a statistically significant reduction in the severity of stomach ulcers and histological damage score. The administration of melatonin at a dose of 20 mg/kg to the pre-treated group reduced inflammatory and oxidative stress markers (IL-1β and MDA) levels similar to those observed with the reference medication.Conclusions: Melatonin alone or a combination of pioglitazone and melatonin effectively reduce gastric mucosal injury, oxidative stress, and pro-inflammatory cytokine levels, comparable to standard omeprazole drugs.